Screened prevalence of trichotillomania and its association with self-esteem among Saudi medical students: a cross-sectional study - Alghamdi, Saleh A. (Frontiers in Psychiatry, 2025)
IntroductionTrichotillomania is a chronic psychiatric syndrome characterized by an uncontrollable urge to pull out one’s hair. The current diagnostic criteria for Trichotillomania are as follows: hair pulling that leads to hair loss; attempts to reduce or stop hair pulling; significant distress or impairment; and the pulling cannot be attributed to another mental or physical condition.AimThe major objective of the study was not to formulate an official clinical diagnosis but to get a preliminary understanding of the prevalence of Trichotillomania symptoms and their possible impact on self-esteem in the medical students in Saudi Arabia by using a self-reported checklist based on DSM-5 criteria.Subjects and methodsThis cross-sectional study was conducted among medical students across various regions of Saudi Arabia. Data were collected through a self-administered online questionnaire designed to ensure broad accessibility and participation. The survey consisted of three main components: (1) sociodemographic information, including age, gender, marital status, and other relevant background variables; (2) a screening checklist based on the DSM-5 diagnostic criteria for Trichotillomania; and (3) the Rosenberg Self-Esteem Scale, used to assess participants’ levels of self-esteem.ResultsThe response rate was 439 (114%), and of the 439 medical students, 50.1% were females, and 64.2% were aged between 18 and 20 years. 39.4% had low self-esteem. The screened prevalence of Trichotillomania in this study was 11.4%. Trichotillomania was higher in Saudi nationals, those who had been married, those who had previously heard of Trichotillomania diagnosis, and those with low self-esteem. In multivariate regression analysis, having heard of Trichotillomania diagnosis and low self-esteem were identified as the significant independent risk factors for Trichotillomania.ConclusionMore than ten percent of medical students through this screening have shown symptoms of Trichotillomania. Symptoms of Trichotillomania potentially affect the mental conditions of students, including self-esteem. The screening has shown that the Trichotillomania was higher in females than males, but the difference was insignificant. Longitudinal studies are needed to extract more data about the Trichotillomania prevalence and its relative impact on mental health conditions.